Trinidad & Tobago: National Agricultural Marketing and Development Corporation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The National Agricultural Marketing and Development Corporation (Namdevco), an agency within the Ministry of Agriculture, Land and Marine Resources, aims to achieve and maintain a commercially viable agribusiness sector by identifying new market opportuni